In vivo and in vitroevaluation of the Acrocomia aculeatapulp oil - lipid profile and oxidative stress - Jacobowski, Ana Cristina; Colin-Gonzalez, Ana Laura; Paz-Loyola, Ariana Lizbeth; Santamaria, Abel; Macedo, Maria LigiaRodrigues (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
Acrocomia aculeata is a plant species with high levels of antioxidant compounds, rich in carotenoids with high bioavailability and monounsaturated fatty acids. This study was designed to investigate the biological effect of Acrocomia aculeata pulp oil (AaPO) on body weight, epididymal adipose tissue mass, liver weight and blood analytes of high-fat-diet-induced obeseC57BL/6j mice.In addition, the antioxidant properties of AaPO were evaluated against the iron sulfate (FeSO4)-induced oxidativedamage to rat brain synaptosomes. Obese mice receiving oral gavage with AaPO showed a significant decrease in body weight, adipose tissue weight,plasma triacylglycerol and aspartate aminotransferase. Histological analysis showed that AaPO attenuated high-fat-diet-induced liver injury decreasing hepatic steatosis and adipocyte hyperplasia. In addition, the in vitro assays showed that AaPOprevented the FeSO4-induced oxidative damage in synaptosomal fractions. Results from this study suggest that AaPO can reduce body weight, plasma triacylglycerol, adipose tissue and oxidative stress.